Ответы и объяснения

  • Участник Знаний
2013-11-24T13:42:47+04:00
1)(11+2 \sqrt{30} -11+2 \sqrt{30} )/(121-120)=4 \sqrt{30}
2)45+6*5 \sqrt{3} +15-10*3 \sqrt{3} =60
3)(6 \sqrt{3} -0,5 \sqrt{6} +4 \sqrt{3} ):0,5 \sqrt{3} =10 \sqrt{3} :0,5 \sqrt{3} -0,5 \sqrt{6} :0,5 \sqrt{3} =20- \sqrt{2}
4)x^1/2*x^1/10_x^1/5*x^1/10-56=0
x^0,6-x^0,3-56=0
x^0,3=a
a^2-a-56=0
a=8,x^0,3=8,x=8^10/3=2^10=1024
a=-7,x^0,3=-7,x=корень третьей степени из (-7):10=-343 \sqrt[3]{7}
5) Все выражение ((х-3)/(5-х))^1/5 обозначим за у
у+1/У=2
у^2-2у+1=0
(y-1)^2=0
y-1=0
y=1
((х-3)/(5-х))^1/5=1
(х-3)/(5-х)=1
х-з=5-х
2х=8
х=4
6.( х+6)^2=(3x+2)(x-0,6)
x^2+12x+36=3x^2-1,8x+2x-1,2
2x^2-11,8x-37,2=0
x^2-5,9x-18,6=0
D=34,81+74,4=109,21
x1=(5,9- \sqrt{109,21} )/2
x2=(5,9+ \sqrt{109,21} )/2




благодарю! ну там х+6/ (х-0,6)^0.5= корень из (3x+2).
Комментарий удален